2013
DOI: 10.1597/11-262.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Cephalometric Morphology and Later Need for Orthognathic Surgery in 6-Year-Old Children with Bilateral Cleft Lip and Palate

Abstract: Six-year-old children with bilateral cleft lip and palate (BCLP) were examined to evaluate the need for orthognathic surgery later in life and to cephalometrically compare the craniofacial morphology of those needing orthognathic surgery with those not needing surgery. Design Retrospective longitudinal study. Patients Thirty-eight consecutive nonsyndromic patients with BCLP (29 boys). Main Outcome Measures Children with BCLP were analyzed from lateral cephalograms taken at a mean age of 6.1 years (range 5.8 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Identifying these patients early in life is important as it can help tailor their treatment so that treatment efficacy is maximized and patient and family suffering reduced. “At risk” patients can be identified early, even at the age of 6 years, as having an ANB angle of less than 7° [Heliövaara et al, ]. At the age of 8 years our group of BCD syndrome patients had a mean ANB angle of 0.7°, indicating a great need for prolonged and lengthy treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Identifying these patients early in life is important as it can help tailor their treatment so that treatment efficacy is maximized and patient and family suffering reduced. “At risk” patients can be identified early, even at the age of 6 years, as having an ANB angle of less than 7° [Heliövaara et al, ]. At the age of 8 years our group of BCD syndrome patients had a mean ANB angle of 0.7°, indicating a great need for prolonged and lengthy treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The revision rate in non-NAM treated patients in our study was, however, not significantly different from the revision rate reported in other studies. [24][25][26][27][28][29][30][31][32][33][34][35][36] In addition, analyses were limited by a small sample size in non-NAM group, especially among patients with BCLP. To account for this fact, we provided analyses using meta-analytic averages, which show even stronger support for a lowered risk of revision among NAM-prepared patients.…”
Section: Discussionmentioning
confidence: 99%
“…The success of speech outcomes corresponds to the patient's preoperative craniofacial morphology. 12,13 Preoperative morphology has primarily been assessed in the orthognathic and dental literature and focused on anterior craniofacial structures. 13 Craniofacial soft tissue structures and their functions have further been a focus of recent studies 14-18 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Preoperative morphology has primarily been assessed in the orthognathic and dental literature and focused on anterior craniofacial structures. 13 Craniofacial soft tissue structures and their functions have further been a focus of recent studies 14-18 . Specifics of the craniofacial structures and the upper cervical spine along with changes across the age span as they relate to surgical outcomes warrant further analysis.…”
Section: Introductionmentioning
confidence: 99%